Feng-shui: Elemen Budaya Tionghoa Tradisional - Kustedja, Sugiri; Sudikno, Antariksa; Salura, Purnama (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2012)
It has been contextual nowadays to observe the traditional feng-shui theory currently  becoming popular topic of discussion. The discussion covers the stake holders in building industry, developers, home owners, professionals, and among the academics of architecture education in the universities. What is the essence of the feng-shui concept? This paper approaches this topic from the different aspects of culture, socio-history, anthropology, ethnography, semiotics, and hermeneutic. It analyses in brief about its history, the major premises in feng-shui, any changes through the Chinese cultural history timeline,  the application tools to transfer the concept into real construction, the persistence of feng-shui in modern life, and the discussions within current contextual situation.